2016
DOI: 10.11118/actaun201664041139
|View full text |Cite
|
Sign up to set email alerts
|

Yields of Selected Catch Crops in Dry Conditions

Abstract: HANDLÍŘOVÁ MARTINA, PROCHÁZKOVÁ BLANKA, SMUTNÝ VLADIMÍR. 2016. Yields of Selected Catch Crops in Dry Conditions. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 64(4): 1139-1148.Catch crops mainly reduce soil erosion and leaching of nutrients as well as enrich the soil organic matter. The aim of this research is to evaluate the yields of catch crops of Sinapis alba, Phacelia tanacetifolia, Fagopyrum esculentum, Carthamus tinctorius and Secale cereale v. multicaule, and thus determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[19]. Furthmore, Handlířová et al [25] found that, in an agroecosystem with a high average annual temperature and low rainfall totals, phacelia achieves higher and more stable yields compared to Fagopyrum esculentum Moench. In a Petri dish experiment designed to measure the palatability of organic matter of various stubble plants for earthworms Lumbricus terrestris L., Kliszcz, Puła [26] proved that during the first 24 h of breeding the soil-phacelia mixture the substrate uptake rate was the fastest by earthworms.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. Furthmore, Handlířová et al [25] found that, in an agroecosystem with a high average annual temperature and low rainfall totals, phacelia achieves higher and more stable yields compared to Fagopyrum esculentum Moench. In a Petri dish experiment designed to measure the palatability of organic matter of various stubble plants for earthworms Lumbricus terrestris L., Kliszcz, Puła [26] proved that during the first 24 h of breeding the soil-phacelia mixture the substrate uptake rate was the fastest by earthworms.…”
Section: Introductionmentioning
confidence: 99%